Shape Optimization of an Airfoil in Ground Effect for Application to WIG Craft. (8th December 2014) - He, Yilei; Qu, Qiulin; Agarwal, Ramesh K.
Abstract : This paper employs a multiobjective genetic algorithm (MOGA) to optimize the shape of a widely used wing in ground (WIG) aircraft airfoil NACA 4412 to improve its lift and drag characteristics, in particular to achieve two objectives, that is, to increase its lift and its lift to drag ratio. The commercial software ANSYS FLUENT is employed to calculate the flow field on an adaptive structured mesh generated by ANSYS ICEM software using the Reynolds-Averaged Navier-Stokes (RANS) equations in conjunction with a one equation Spalart-Allmaras (SA) turbulence model. The results show significant improvement in both the lift coefficient and lift to drag ratio of the optimized airfoil compared to the original NACA 4412 airfoil. It is demonstrated that the performance of a wing in ground (WIG) aircraft can be improved by using the optimized airfoil.